Energy and elemental composition (C, N, H) in growing megalopa of an edible crab Charybdis variegata (Fabricus) - Kumaresan, S; Soundarapandian, P; Karuppiah, S P; Kannupandi, T (Indian Journal of Fisheries, 2011)
The larval development of Charybdis variegata consists of five zoeal and onemegalopa stages. The megalopa stage appears as a miniature adult or a preadult.Hence a radical change is expected functionally in the form of changes inbiomass-dry weight, energy, elemental composition (C, N, H), respiration andexcretion. In the laboratory, the dry weight of individual megalopa increased from226.18 to 439.22 ug, carbon increased from 73.80 to 166.70 ug/ind, hydrogen andnitrogen content range was from 10.12 to 22.6 ug and 17.9 to 39.18ug respectively.C : N ratio in the 0 day was 4.0:1.0 and in 6th day it was 4.1:1.0. C : H ration in the0 day was 7.2 : 1.0 and in 6th day it was 7.3 : 1.0.